Bases genéticas de caracteres quantitativos em diferentes populações de aveia (Avena sativa L.) - Valério, Igor Pirez (2006)
In the investigations performed with the oat crop, many mechanisms have been proposed with the goal of maximizing the genetic gains in different quantitative traits, especially on segregating populations, where a greater level of genetic interaction is expected. On the other hand, great value has been attributed to the right choice of environmentally adapted genotypes, increasing the potential of making the best selections. The research had, as a general goal, to determine the genetic parameters of quantitative traits in oats, with the choice of parents and genotypes with high yield potential and predictable behavior. Two experiments were carried on: the first consisted on a stability test of different oat populations based on the general and specific combining ability estimates from five genotypes. The results indicate the great potential of the evaluated genotypes for the breeder s use aiming to infer about general combining ability, showing high predictability in their performances. However, on identifying the best genotypes by specific combining ability effects, evaluations in different generations and years was essential for obtaining more precise results. Nevertheless, specific crosses between oat genotypes can be efficient for traits related to grain yield, via indirect selection for the trait. Based on the statistical parameters evaluated, as observed for UPF 16 / UPF 18, UPF 16 / UFRGS 17 and UPF 16 / UFRGS 7, for number of panicles pe plant, panicle weight and number of grains per plant, respectively. The second experiment aimed to estimate the genetic parameters involved in the trait grain yield and its components, through the analysis of different generations, supplying tools for the selection of high yield potential genotypes at early selfing generations. Significant epistatic interaction can be observed for the trait grain yield per plant and those are essential for the understanding of the genic effects involved in each cross. On the other hand, the results suggest that specific crosses between oat genotypes can result in large gains for the selection at early generations, as seen for grain yield per plant for UPF 16 / UPF 18 and UPF 18 / UFRGS 7. These crosses presented only the interaction additive x additive as a significant epistatic effect, being able to produce larger genetic gains. Additionally, the traits number of panicles per plant and panicle weight showing lower complexity on the estimated genic effects, being their selection more effective. Thus, the cross UPF 18 / UFRGS 17, calls for attention, since the dominance effect is non significant, even if the cross presents a larger participation of dominance variance in the genetic variance of the trait. Regarding the trait panicle weight, the cross UPF 18 / UFRGS 7 can be highlighted, because it shows a higher participation of the additive comparing to the dominance effect on the genetic control of the trait.